An Introduction to the Table of Plants - Yakir, Michal (Homœopathic Links, 2016)
The Table of Plants is a botanic, systematic approach to plant remedies, based on the botanic evolution sequence of plants that creates vectors of development, and thus invites us to arrange it in an easy to understand table. The Table is grouping of plant remedies on Family and the higher level of Order, rather than the remedy level, allowing for a comprehensive overview of all our ‘botanic’ materia medica in a way which relates to human evolution and the places that stopped evolving—namely diseases. The Table is a way of looking at our materia medica—not a new system—and can be easily integrated in our practice, leading to easier prescriptions and deeper understanding of our own cases.
Keywords: table of plants; systematic homeopathy; botanical approach to plant remedies; plant families and orders; plant phenotype; human evolution; Hamamelis virginica